Numerical Investigation of Two-phase Unstable Combustion in High Temperature Rise Flame Tube. Issue 1 (1st May 2022) - Long, Wang; Ren, Jiande; Cai, Wenxiang; Chen, Xiong
Abstract: Intense acoustic pressure oscillation, caused by instability combustion, poses a huge challenge for the performance and the structural integrity of high temperature rise combustor. Transient process of combustion in the flame tube with three-stage axial swirler was investigated by numerical methods. Simulation results show that a wide range of velocity fluctuations appear at swirler's outlet and recirculation zone move periodically at flame tube's circumferential center plane, which cause the oscillation combustion.